2020
DOI: 10.1016/j.oceaneng.2020.108081
|View full text |Cite
|
Sign up to set email alerts
|

Multi-phase fluid flow simulation by using peridynamic differential operator

Abstract: The problems of multi-phase fluid flows are often encountered in engineering. In this study, a non-local numerical model of multi-phase fluid flows in the Lagrangian description is developed. Based on the peridynamic theory, a peridynamic differential operator is proposed which can convert any arbitrary order of differentials into their integral form without calculating the peridynamic parameters. Therefore, the Navier-Stokes equations including the surface tension forces are reformulated into their integral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 83 publications
(152 reference statements)
1
3
0
Order By: Relevance
“…Overall, a good agreement is found between our computed responses and the results obtained in literature. 74 Note also that Figure 9 depicts consistent numerical results for two different approximation domain sizes in (18).…”
Section: Koyna Damsupporting
confidence: 60%
See 3 more Smart Citations
“…Overall, a good agreement is found between our computed responses and the results obtained in literature. 74 Note also that Figure 9 depicts consistent numerical results for two different approximation domain sizes in (18).…”
Section: Koyna Damsupporting
confidence: 60%
“…where Δx is the spacing in a uniform grid and r denoting the size of approximation domain. For small deformation problems considered in this article, it is found that the size of approximation domain r in (18) does not influence the results significantly. An example will be provided later in Section 7.1.1.…”
Section: Approximation Of Strain Fieldmentioning
confidence: 76%
See 2 more Smart Citations